UK national bladder outlet obstruction surgery snapshot audit. (28th October 2021) - Aning, Jonathan J.; Calvert, Robert C.; Harding, Chris; Fowler, Sarah; Nitkunan, Tharani; Lee, Su‐Min; McGrath, John S.; Cresswell, Joanne; Hagan, Patricia; Hermans, Louisa; Dickinson, Andrew J.
Abstract : Objectives: To determine the preoperative assessment and perioperative outcomes of men undergoing bladder outlet obstruction (BOO) surgery in the UK. Patients and Methods: A retrospective cohort study was conducted of all men undergoing BOO surgery in 105 UK hospitals over a 1‐month period. The study included 1456 men, of whom 42% were catheter dependent prior to undergoing surgery. Results: There was no evidence that a frequency–volume chart or urinary symptom questionnaire had been completed in 73% or 50% of men, respectively in the non‐catheter‐dependent group. Bipolar transurethral resection of the prostate (TURP) was the most common BOO surgical procedure performed (38%). Monopolar TURP was the next most prevalent modality (23%); however, minimally invasive BOO surgical procedures combined accounted for 17% of all procedures performed. Of the cohort 5% of men had complications within 30 days of surgery, only 1% had Clavien–Dindo Grade ≥III complications. Less than 1% of the cohort received a blood transfusion after BOO surgery and 2% were re‐admitted to hospital after their BOO surgery. In total only 4% of the whole cohort were catheter dependent after BOO surgery. Pre‐ and postoperative paired International Prostate Symptom Score scores reviewed suggest that minimally invasive surgical procedures achieved comparable levels of improvement in both symptoms and bother at 3 months postoperatively in men who were not catheter dependent preoperatively. Conclusions: There has been a substantial shift in the available choice of procedure for BOO surgery around the UK in recent years. However, men can be reassured that overall BOO surgery treatments are safe and effective. Evidence of adherence to guidelines in the preoperative assessment of men with lower urinary tract symptoms undergoing surgery was poorly documented and must be improved.